2013
DOI: 10.1111/tpj.12258
|View full text |Cite|
|
Sign up to set email alerts
|

Hexokinase mediates stomatal closure

Abstract: SUMMARYStomata, composed of two guard cells, are the gates whose controlled movement allows the plant to balance the demand for CO 2 for photosynthesis with the loss of water through transpiration. Increased guardcell osmolarity leads to the opening of the stomata and decreased osmolarity causes the stomata to close. The role of sugars in the regulation of stomata is not yet clear. In this study, we examined the role of hexokinase (HXK), a sugar-phosphorylating enzyme involved in sugar-sensing, in guard cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
264
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 189 publications
(279 citation statements)
references
References 67 publications
15
264
0
Order By: Relevance
“…This has also been described previously by transpiration (Lu et al, 1997;Outlaw 2003;Kang et al, 2007;Kelly et al, 2013;Lawson et al, 426 2014;Daloso et al, 2016). However, no significant acclimation of the slow decrease in A and 427 g s through the day by growth light intensity and pattern was observed in this experiment.…”
supporting
confidence: 82%
“…This has also been described previously by transpiration (Lu et al, 1997;Outlaw 2003;Kang et al, 2007;Kelly et al, 2013;Lawson et al, 426 2014;Daloso et al, 2016). However, no significant acclimation of the slow decrease in A and 427 g s through the day by growth light intensity and pattern was observed in this experiment.…”
supporting
confidence: 82%
“…Importantly, it was shown that catalytically inactive HXK1 mutant forms still have a signaling function, supporting the view that the role of HKX1 in signaling high sugar availability is independent of its role in Glc metabolism (Moore et al, 2003). More recent work has shown that HXK1 also mediates stomatal closure, thereby contributing to the feedback effect of sugar accumulation on photosynthesis (Kelly et al, 2012;Kelly et al, 2013).…”
mentioning
confidence: 54%
“…Initially proposed by Outlaw and coworkers (Outlaw and Manchester, 1979;Lu et al, 1995Lu et al, , 1997Ewert et al, 2000;Outlaw and De Vlieghere-He, 2001;Kang et al, 2007), Suc generated by mesophyll photosynthesis is uploaded to the phloem and transported away from sources to sinks driven by transpiration (Outlaw and De Vlieghere-He, 2001). Excess Suc (when photosynthesis is high) is carried toward the stomata by the apoplast, stimulating stomatal closure either through some signaling mechanism or by acting as an osmoticum (Lu et al, 1997;Outlaw, 2003;Kang et al, 2007;Kelly et al, 2013). Such a process could only occur over longer time scales, as high rates of photosynthesis are not associated with low g s ; however, decreases in g s often are seen toward the end of the diurnal period, despite environmental conditions being similar to morning conditions .…”
Section: Mechanisms Of Coordination Between Stomatal Behavior and Mesmentioning
confidence: 99%
“…Over the diurnal period, a number of species display a decrease in g s and A that is not driven by decreases in light intensity or the temporal response of g s (Mott and Parkhurst, 1991;Allen and Pearcy, 2000;Mencuccini et al, 2000;Moriana et al, 2002;Dodd et al, 2006;de Dios et al, 2012), but the exact mechanism for this requires further investigation. As discussed earlier, sugar accumulation due to high A is believed to provide a long-term photosynthetic feedback on g s (Lu et al, 1995(Lu et al, , 1997Outlaw, 2003;Kang et al, 2007;Kelly et al, 2013), which also needs to be taken into account when considering the incorporation of temporal responses into models of stomatal behavior. Noe and Giersch (2004) proposed a model based on the assumption that the pool of sugars, resulting from the difference between the rate of sugar production by photosynthesis and their rate of export, increasingly inhibited A over the diurnal period.…”
Section: Diurnal Impact On Stomatal Behavior and Implications For Futmentioning
confidence: 99%